Gampong Aware of Stunting Through Strengthening Health Posts Based on Technology Transfer in Alue Naga, Syiah Kuala District, Banda Aceh - Lydia Septa Desiyana; Febia Sari; Marisa; Novince Kadepa; Naila Salsabila (Pascasarjana Universitas Mataram, 2025)
Stunting is a chronic nutritional problem that has long-term impacts on a child's physical and cognitive development. The Indonesian Nutrition Status Survey (SSGI) and the Indonesian Health Survey (SKI) reported that the incidence rate of stunting in Banda Aceh in 2023 was 21.7% (Diskominfo Banda Aceh, 2024). This prevalence rate has decreased compared to the previous year, but the achievement in 2024 still does not meet the target set by the Aceh government, which is 14% (Aceh Social Service, 2024). This highlights the urgency of this activity. The goal of the service is to provide direct and interactive education to the community and to enhance the capacity of posyandu counselors through training, as well as to conduct technology transfer in the form of modules and educational videos about stunting. This service has carried out technology transfer in the form of modules and educational videos about stunting, which are used in training health post counselors with the aim of increasing the knowledge and skills of cadres in educating the community. The measurement results show that training and technology transfer in the form of modules and educational videos increased the knowledge, attitudes, and behaviors of cadres and the community (p<0.05). Strengthening the implementation of this service needs to be carried out through improvements in posyandu procedures and regular monitoring and evaluation. Replication of this service can also be implemented to support program expansion and sustainability.